Cultivation and identification of selected wild edible mushroom (Lentinus sp.) grown on sawdust substrate - Takril, Nurul-Fatini (2017)
Mushrooms have been consumed since in the earliest history. Mushrooms are famous and a valuable source of food. Currently, the variety of mushrooms in Malaysian markets is not as diverse as those actually found on earth. Some of the mushrooms sold at retail stores in Malaysian markets are Auricularia polytricha (Black jelly mushroom), Pleurotus ostreatus (Oyster mushroom), Pleurotus sajor-caju (Grey oyster mushroom) and Pleurotus florida (White Oyster mushroom). Therefore, one of the efforts to support the situation is to increase the variety of mushroom species in local markets. Malaysia is situated in a tropical region that is supported by diverse habitats which very suitable for the growth of various types of wild mushrooms. Interestingly, a number of wild mushrooms under genus Lentinus are widely used as food and they possessed therapeutic properties. A number of Lentinus species such as L. squarrosulus, L. sajor-caju, and L. strigosus have been reported as edible. Although Lentinus species are reported as edible, they are not yet cultivated in Malaysia as commercial mushrooms. Thus, the objectives of this study are 1) to identify the morphological characteristics of Lentinus species, 2) to isolate and cultivate pure culture mycelia of Lentinus species, and 3) to evaluate the biological efficiency of Lentinus species grown on sawdust substrate. The wild edible Lentinus were collected along the rivers in Selangor areas. The pure culture was isolated from the fruiting bodies. Spawns of Lentinus were grown on sawdust substrate. The yield of fruiting bodies was observed. This study introduces the cultivation of wild mushroom species that have a potential to commercialize as an edible mushroom for future of mushroom industry in Malaysia.